(untitled) (Práxis Educativa, 2015)
The article is a contribution to the field of studies on textbooks. It analyzes the changes and continuities recorded in the “comprehensive manuals” by the Kapelusz publisher for the elementary education in Argentina between 1976 and 2001. A sample of manuals for the fourth grade published by that publisher is analyzed. The contents of social sciences, specifically History, are reviewed here. The article analyzes the changes in the manuals and their evolution is compared at the intra-publisher level. Among other aspects, the permeability of the education policy concerns of that time is noticed in the manuals. “Formal changes” in the manuals are also analyzed. With the aid of edition software, the characters in the texts are counted and a reduction is noticed due to the written texts being replaced by a larger number of images. Keywords: Comprehensive manuals. Kapelusz publisher. Changes.